An analytical method to predict the buckling and collapse behaviour of plates and stiffened panels under cyclic loading. (15th November 2019) - Li, Shen; Hu, Zhiqiang; Benson, Simon
Highlights: Cyclic progressive collapse of ship structures. Parametric finite element analysis of steel plates under cyclic compression/tension. Analytical method to predict the cyclic load-shortening curves. A validation on unstiffened plates and stiffened panels. Abstract: The nonlinear stress-strain relationship of a thin plate or stiffened panel under in-plane load is represented by a load-shortening curve. The curves are used to evaluate the buckling and ultimate collapse behaviour of these structural elements, and furthermore forming the input data to analytical progressive collapse methods for large scale box girder structures such as ships. This paper develops a novel analytical method that predicts the load-shortening curve of plates and stiffened panels under cyclic in-plane load. This provides the framework to account for load reversals in an enhanced cyclic progressive collapse method. A parametric study using nonlinear finite element analysis is completed to investigate the characteristic behaviour of simply supported plates under cyclic compression and tension. The investigation covers a range of aspect ratios and slenderness ratios typical for ship-type structures. Single-cycle and ten-cycle loading protocols are applied, which demonstrate progressive reduction in strength and stiffness together with a response convergence after several cycles. An analytical method to predict multi-cycle load-shortening behaviour is then derived using a response and updating rule based on the observed characteristics from the parametric study. A validation of the analytical method is performed on a range of unstiffened plates and stiffened panels under various cyclic loading protocols. A good comparison with the results of finite element analysis is obtained, which confirms the validity of the proposed analytical method.